Filling the gaps in epistemological belief research on Muslims - Fasehah Muhamad, Nurul Asiah; Mohd Zhaffar, Nursafra; Jaafar, Noornajihan (Opción, 2019)
The paper aims to provide a general view of the model of Islamic epistemological beliefs for Muslims which become the based for the development of constructs, subconstructs and item for Islamic epistemology belief Questionaires (MEBQs) together with some large gaps in the study of epistemology beliefs for Muslims via comparative qualitative research method. The results showed similarity with Mahfuzah (2016) where the construct of source of knowledge become one of the important construct to determined one’s Islamic epistemological belief. In conclusion, this paper presents a basic model of epistemological beliefs derived from Islamic tasawur, where MEBQ was the basis.